Hospitalist perspectives on buprenorphine treatment for inpatients with opioid use disorder - Megan K Reed; Vignesh Murali; Nazanin Sarpoulaki; Jillian H. Zavodnick; Jeffrey K. Hom; Kristin L Rising (Drug and Alcohol Dependence Reports, 2022)
Background: Patients with opioid use disorder (OUD) have high hospital admission rates. Hospitalists, clinicians that work in inpatient medical settings, may have a unique opportunity to intervene on behalf of these patients, yet their experience with and attitudes towards treating patients with OUD need further exploration. Methods: We conducted qualitative analysis of 22 semi-structured interviews with hospitalists between January and April 2021 in Philadelphia, PA. Participants were hospitalists in one major metropolitan university hospital and one urban community hospital in a city with a high prevalence of OUD and overdose deaths. Participants were asked about their experiences, successes, and difficulties in treating hospitalized patients with OUD. Results: Twenty-two hospitalists were interviewed. Participants were majority female (14, 64%) and White (16, 73%). We identified the following common themes: lack of training/experience with OUD, a lack of community OUD treatment infrastructure, a lack of inpatient OUD/withdrawal treatment resources, the “X-waiver” as a barrier to prescribing buprenorphine, the “ideal” patient to start on buprenorphine, and the hospital as an ideal intervention setting. Conclusions: Hospitalization due to acute illness or complication of drug use represents a potential intervention point to initiate treatment for patients with OUD. While hospitalists exhibit willingness to prescribe medications, provide harm reduction education, and link patients to outpatient addiction treatment, they identify training and infrastructure barriers that must first be addressed.